4-year results from the RAPID-PsA phase 3 randomised placebo-controlled trial of certolizumab pegol in psoriatic arthritis. Issue 1 (14th March 2018) - van der Heijde, Désirée; Deodhar, Atul; FitzGerald, Oliver; Fleischmann, Roy; Gladman, Dafna; Gottlieb, Alice B; Hoepken, Bengt; Bauer, Lars; Irvin-Sellers, Oscar; Khraishi, Majed; Peterson, Luke; Turkiewicz, Anthony; et al.
Abstract : Objective: To report the efficacy, patient-reported, radiographic and safety outcomes of 4 years' certolizumab pegol (CZP) treatment in patients with psoriatic arthritis (PsA). Methods: RAPID-PsA (NCT01087788 ) was double-blind and placebo-controlled to Week 24, dose-blind to Week 48 and open-label (OL) to Week 216. Patients were randomised 1:1:1 to either placebo or CZP 200 mg every 2 weeks (Q2W) or 400 mg every 4 weeks (Q4W) (following 400 mg at Weeks 0/2/4). Patients randomised to CZP continued their assigned dose in the OL period. Patients randomised to placebo were re-randomised to CZP 200 mg Q2W or 400 mg Q4W (post-loading dose) at Week 16 (early escape) or after the double-blind phase. We present observed and imputed data; missing values were imputed using non-responder imputation (NRI) for categorical and last observation carried forward (LOCF) for continuous measures. Results: 409 patients were randomised; 20% (54/273) of Week 0 patients randomised to CZP had prior anti-tumour necrosis factor (TNF) exposure; 67% (183/273) completed 216 weeks. By Week 48, 60.4% of patients achieved Disease Activity Index for Psoriatic Arthritis low disease activity or remission, which was maintained; 66.3% achieved these outcomes at Week 216 (NRI). At Weeks 48 and 216, 39.2% of patients achieved minimal disease activity (NRI). 75% reduction in Psoriasis Area and Severity Index responses were 65% and 52% at Weeks 48 and 216 (NRI). Total resolution rates for enthesitis, dactylitis and nail psoriasis, at 4 years, were 71%, 81% and 65%, respectively (LOCF). Structural damage progression was low over 4 years' treatment. No new safety signals were identified after Week 96. Conclusions: CZP efficacy in treating PsA was maintained over 4 years, in patients both with and without prior anti-TNF exposure, with no new safety signals identified.